Faktor-Faktor yang Memengaruhi Penanaman Modal Dalam Negeri di Indonesia Menurut Provinsi Tahun 2014-2023 - Hermawan, Kadek Dody Kusuma (Seminar Nasional Official Statistics, 2025)
Domestic Investment (DI) is one type of investment that comes from local investors. This study aims to determine the factors that influence DI in Indonesia by province 2014-2023. This study uses panel data obtained from Statistics Indonesia and Ministry of Manpower. The data consists of variables of DI realization, Gross Regional Domestic Product (GRDP), Provincial Minimum Wage (PMW), inflation, and Incremental Capital Output Rasio (ICOR). These variables were modeled with panel data regression. The model selection results show that Fixed Effect Model (FEM) is the most suitable model to explain the influence of independent variables on DI realization. The estimation results show that variables of GRDP and PMW each have a positive and significant effect on DI realization, while variables of inflation and ICOR have no effect. These findings can provide insights for the government in formulating policies to create more equitable DI realization